Hitchcock e a arquitectura - Sara Filipa Teixeira Pinto (2012)
How does architecture contribute to the films of Alfred Hitchcock? And how do thespaces that he designs and films help in creating the atmospheres that made his moviesfamous?This paper proposes a reflection on cinema's architecture, basing itself on Hitchcock'sfilmography.Gaston Bachelard, in La Poétique de l'Espace , said that the most precious benefactionof the house is that it accommodates dreaming, protects the dreamer, and allows us todream in peace. However, this safety of the house and the home was something thatHitchcock enjoyed to subvert. To really get in touch with the viewers most primitiveemotions, like fear itself, he thought it would be more effective to invert what we wouldusually consider a safe place. It is said that Hitchcock liked to play the public's emotionslike the keys of an organ, but what is interesting is to try to understand how the filmmakerused filmed space and lighting in order to indeed manipulate the human psyque.How did Hitchcock influence the perception of space and of certain architecturalelements as well as their symbolic meanings? The bathroom, the tub, and the showercurtain, were never the same after Psycho , nor motels as frightening. Church towers havenever been as vertiginous as in Vertigo , or the windows as indiscreet as in Rear Window .